ANALISIS PERILAKU MASYARAKAT TERHADAP KEBIJAKAN PEMBIAYAAN BANK SYARIAH (STUDI DI DESA KAREHKEL, DESA LEUWIMEKAR DAN DESA BARENGKOK KECAMATAN LEUWILIANG, KABUPATEN BOGOR, JAWA BARAT) - Fauzi Rahman, Muhammad Wildan; Thantawi, Tubagus Rifqy; Anwar, Miftakhul (Jurnal Penelitian Perbankan Syariah: Program Studi Perbankan Syariah., 2024)
Customer behavior is an activity that discusses and explains how to make decisions both individually and in groups to determine decisions to use or make purchases of a product, in this case an assessment of Islamic banking financing policies. The main objective of this study is to analyze customer behavior in taking financing at Islamic banks. This study used a proportionate stratified random sampling technique. Data collection was carried out by library research, documentation study and observation. The results of this study prove that customer behavior has a positive and significant influence of 86.1% on Islamic banking policies. The realization of these sharia banking policies is based on the behavior of customers who want these sharia banking policies to provide customer trust and satisfaction.